Assessment of websites of Polish landscape parks - Zbaraszewski, Wojciech (Ocena serwisów internetowych polskich parków krajobrazowych, 2020)
The purpose of the article is to evaluate the websites of Polish landscape parks in terms of information (presence and quality) and technical aspects (loading speed, availability, responsiveness) including functional development stages. The study concerned all (125) Polish landscape parks. The research consisted in assessing the websites of landscape parks according to the adopted 37 consolidated criteria which formed the basis for distinguishing 4 stages of functional development of websites. As a result of the study, the hypothesis that Polish landscape parks do not use the full potential of modern information and communication technologies on their websites, was positively verified.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 131-141
Keywords: landscape park; nature protection; tourism; websites; websites assessing criteria; sustainable development